2013
DOI: 10.1002/hed.23271
|View full text |Cite
|
Sign up to set email alerts
|

Combined transoral robotic tongue base surgery and palate surgery in obstructive sleep apnea‐hypopnea syndrome: Expansion sphincter pharyngoplasty versus uvulopalatopharyngoplasty

Abstract: As the palate component of our multilevel procedure, expansion sphincter pharyngoplasty, including conventional nose surgery and robotic surgery, seems to be superior to uvulopalatopharyngoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 12 publications
3
63
0
1
Order By: Relevance
“…In 2007, Pang et al [6] had showed an 82.6 % success rate (with 50 % reduction of pre-operative AHI and AHI \ 20) in their randomized controlled clinical trial. Vicini et al in their perspective multi-level sleep apnea surgery with palate and trans-oral robotic surgery (TORS) tongue base resection, showed that their initial post-operative data (when they used the traditional uvulopalatopharyngoplasty technique with the trans-oral tongue base resection) was only fair, with a mean postoperative AHI of 19.8 ± 14.1 compared to the expansion pharyngoplasty and the trans-oral robotic tongue base resection, which yielded a post-operative AHI of 9.9 ± 8.6; Vinci et al [16] had maintained the 2 groups controlled for BMI, gender, age, pre-operative AHI and volume of tongue base tissue removed. Carrasco et al had demonstrated in 53 patients who had moderate to severe OSA (mean pre-operative AHI 41.9 ± 24.3), that the expansion pharyngoplasty (pre-operative AHI 27.7 ± 7.5 to post-operative AHI 6.5 ± 5.2) had better results compared to the traditional uvulopalatopharyngoplasty (preoperative AHI 47.3 ± 27.1 to post-operative AHI 12.0 ± 7.1) [17].…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, Pang et al [6] had showed an 82.6 % success rate (with 50 % reduction of pre-operative AHI and AHI \ 20) in their randomized controlled clinical trial. Vicini et al in their perspective multi-level sleep apnea surgery with palate and trans-oral robotic surgery (TORS) tongue base resection, showed that their initial post-operative data (when they used the traditional uvulopalatopharyngoplasty technique with the trans-oral tongue base resection) was only fair, with a mean postoperative AHI of 19.8 ± 14.1 compared to the expansion pharyngoplasty and the trans-oral robotic tongue base resection, which yielded a post-operative AHI of 9.9 ± 8.6; Vinci et al [16] had maintained the 2 groups controlled for BMI, gender, age, pre-operative AHI and volume of tongue base tissue removed. Carrasco et al had demonstrated in 53 patients who had moderate to severe OSA (mean pre-operative AHI 41.9 ± 24.3), that the expansion pharyngoplasty (pre-operative AHI 27.7 ± 7.5 to post-operative AHI 6.5 ± 5.2) had better results compared to the traditional uvulopalatopharyngoplasty (preoperative AHI 47.3 ± 27.1 to post-operative AHI 12.0 ± 7.1) [17].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the multilevel approach is becoming more diffuse in routine surgical practice, especially since the introduction of transoral robotic surgery (TORS) 1 .…”
Section: Introductionmentioning
confidence: 99%
“…It was devised as a transoral robotic modification of Chabolle's open tongue base reduction and hyoid epiglottopexy [2]. At this time, it is estimated that more than 450 transoral robotic surgeries (TORS) for OSAHS have been performed throughout the world; 201 of them have been reported in the literature (table 1) [1,3,4,5,6,7,8]. However, there have been no multi-institutional studies examining the safety and efficacy of TORS.…”
Section: Introductionmentioning
confidence: 99%